Inheritance of toxicity aluminum tolerance on rice based on diallelic analysis - Ferreira, Reinaldo de Paula; Cruz, Cosme Damião; Sediyama, Carlos Sigueyuki; Pinheiro, Beatriz Silveira (Pesquisa Agropecuaria Brasileira, 1999)
Three tolerant (Guarani, Guaporé e IAC 25) and three sensitive (CNA 5600, CNA 5615 e IAC 899) genotypes of rice (Oryza sativa L.) and their respective F1 crosses, obtained in a diallel cross system not accounting the reciprocal crosses, were evaluated to study the inheritance of toxicity aluminum (Al) tolerance. The Al concentration in nutritive solution was 20 mg/L. The results showed that the inheritance is oligogenic with the tolerance determined by the dominant alleles. The parents Guarani, Guaporé and IAC 25 showed greater dominant allele concentration and CNA 5600, CNA 5615 and IAC 899 more recessive alleles.